Efficiency and defense motivated ingroup projection: Sources of protoypicality in intergroup relations - Rosa, M. (2014)
Members of higher status groups generalize characteristics of their ingroup to superordinate categories that serve as a frame of reference for comparisons with outgroups (ingroup projection). We propose that the causal process depends on the security of the intergroup context: When intergroup relations are secure, projection derives from a motivation to represent the superordinate category efficiently; when they are insecure, projection is a defense motivated process. Accordingly, we hypothesized that inducing participants to use heuristic vs. systematic information processing (via time pressure, cognitive load, or thoughtfulness instructions) would have differential effects on ingroup projection in secure as compared to insecure intergroup relations. Three experiments manipulated security of the intergroup context and information processing mode in artificial (Studies 1 and 2) or natural (Study 3) groups. We found that time pressure increased ingroup projection in the secure-group condition but decreased it in the insecure-group condition (Study 1), cognitive load increased projection in the secure but not in the insecure condition (Study 2) and thoughtfulness instructions increased projection for high identifiers in the insecure but not in the secure condition (Study 3). Results support the hypothesis that ingroup projection occurs as a cognitive bias in secure intergroup relations but that it is socially motivated by the specific intergroup relation when this relation is insecure.